2019
DOI: 10.1186/s12887-019-1896-6
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder is associated with gut microbiota disorder in children

Abstract: Background: The aim of this study was to evaluate the occurrence and clinical characteristics of autism spectrum disorder (ASD) associated to the stable state of the gut microbiota. Methods: A total of 9 children with ASD and 6 healthy children used as control were selected and feces samples were collected from all of them. The 16S gene ribosomal RNA sequencing was used to analyze the difference in gut microbiota between healthy control children and ASD patients. Results: The results of 16S sequencing based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…Our results indicated that n-3/n-6 PUFAs (1:5) supplementation improved the behavioral patterns of autistic rats by reducing Firmicutes in their intestines. Sun et al found that the average abundance of Prevotellaceae in the ASD group was lower than in healthy children (25). Our findings showed that the abundance of Prevotellaceae in the VPA group was lower than that in the control group at the genus level.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Our results indicated that n-3/n-6 PUFAs (1:5) supplementation improved the behavioral patterns of autistic rats by reducing Firmicutes in their intestines. Sun et al found that the average abundance of Prevotellaceae in the ASD group was lower than in healthy children (25). Our findings showed that the abundance of Prevotellaceae in the VPA group was lower than that in the control group at the genus level.…”
Section: Discussionsupporting
confidence: 45%
“…The change of intestinal flora in autistic patients mainly, are manifested by the significant increase of intestinal bacterial translocation, the elevated amount of clostridium species, increased Desulfovibrio, and decreased bifidobacteria. Compared with neurotypical children, the intestinal flora abundance is decreased in children with autism (25).…”
Section: Discussionmentioning
confidence: 93%
“…Authors were contacted when the required data were not available. In this regard, although the study by Sun et al [30] met the main inclusion criteria, it was not included in the meta-analysis due to the lack of necessary data and no response from the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Three populations were found to signi cantly increase over time in the boy group: Selenomonadales,Negativicutes and Veillonellaceae. A recent study suggests that lower abundances of Selenomonadales and Veillonellaceae are associated with autism spectrum disorder 39,40 . Dysregulation of Selenomonadales affects gut secretion and in turn affects brain function by modulating the e cacy of the vagal response 41 .…”
Section: Discussionmentioning
confidence: 99%